Olfactory Malformations in Mendelian Disorders of the Epigenetic Machinery - Aleo, Sebastiano; Cinnante, Claudia; Avignone, Sabrina; Prada, Elisabetta; Scuvera, Giulietta; Ajmone, Paola Francesca; Selicorni, Angelo; Costantino, Maria Antonella; Triulzi, Fabio; Marchisio, Paola; Gervasini, Cristina; Milani, Donatella (Frontiers in Cell and Developmental Biology, 2020)
Usually overlooked by physicians, olfactory abnormalities are not uncommon. Olfactory malformations have recently been reported in an emerging group of genetic disorders called Mendelian Disorders of the Epigenetic Machinery (MDEM). This study aims to determine the prevalence of olfactory malformations in a heterogeneous group of subjects with Mendelian Disorders of the Epigenetic Machinery. We reviewed the clinical data of 35 patients, 20 females and 15 males, with a mean age of 9.52 years (SD 4.99). All patients had a MDEM and an already available high-resolution brain MRI scan. Two experienced neuroradiologists reviewed the MR images, noting abnormalities and classifying olfactory malformations. Main findings included Corpus Callosum, Cerebellar vermis, and olfactory defects. The latter were found in 11/35 cases (31.4%), of which 7/11 had Rubinstein-Taybi syndrome (RSTS), 2/11 had CHARGE syndrome, 1/11 had Kleefstra syndrome (KLFS), and 1/11 had Weaver syndrome (WVS). The irregularities mainly concerned the olfactory bulbs and were bilateral in 9/11 patients. With over 30% of our sample having an olfactory malformation, this study reveals a possible new diagnostic marker for MDEM and links the epigenetic machinery to the development of the olfactory bulbs.